Characteristics of the psychopathological status of oral lichen planus: a systematic review and meta‐analysis. (24th January 2022) - Li, K; He, W; Hua, H
Abstract: Oral lichen planus (OLP) is a chronic inflammatory disease of the oral mucosa having no clear aetiology or pathogenesis. The influence of psychological disturbances on OLP has been widely discussed but still bears the controversy. This study aimed at assessing scientific evidence between the OLP and psychological alterations of the patient. We searched seven important databases for studies on OLP and psychological factors (anxiety, depression, stress, sleep disorders, etc.) published between 1 January 2000, and 1 October 2020. Case‐control and cross‐sectional studies were incorporated into this study. The meta‐analysis used a random‐effects model assessed by using the I 2 statistic. Dichotomous variables used the odds ratio and 95% confidence interval (CI), and continuous variables used the mean difference with 95% CI. Finally, 26 studies were included in the review. A meta‐analysis of 13 studies showed there was a significant association of OLP with anxiety, depression and stress compared with healthy controls. Certain personality characteristics and sleep disorders also influence the patient of OLP. Therefore, psychological and psychiatric examinations should be carried out routinely for patients with OLP and improve the prognosis of the disease. © 2022 Australian Dental Association